Analysis and Evaluation of a Searchable Exercise Repository for Training Java Programming - Kok, Arjan J.F; Bijlsma, Lex; Huizing, Cornelis; Kuiper, Ruurd; Passier, Harrie (Informatics in education, 2024)
This paper presents the first experiences of the use of an online open-source repository with programming exercises. The repository is independent of any specific teaching approach. Students can search for and select an exercise that trains the programming concepts that they want to train and that only uses the programming concepts they already know, then submit their solutions, and get automatic feedback from the system. We analyzed quantitatively how students used the system by inspecting the logged actions of the students using the system. We also did a qualitative analysis by interviews, to find out how the students appreciated the use of the repository and to get feedback for improvements. We focused on how students select exercises as finding the exercise that fulfils the training needs of a student is the innovative part of our repository.